Islamic Sharia Signaling and Ex-Ante Determinants of IPO Initial Returns - Karim, Abdul (Inovasi Analisis Data, 2025)
Objective; This paper examines the effect of ex-ante determinants on IPO initial returns and the moderating effect of Shariah compliance. The study combines ethical finance and well-known IPO models to shed new light on under pricing mechanisms.Methods; The study uses a quantitate method of secondary data from IPO prospectus, governance report and financial database. Hypotheses were tested with multiple regression analysis and moderated regression analysis (MRA) and were further supplemented with other robustness checks, and hierarchical regression to establish validity.Results; Results show that market sentiment, oversubscription, certification signals, governance characteristics, and offering attributes form significant determinants of IPO initial return. Moreover, by requiring Shariah compliance, the informational content of these factors is enhanced, investor confidence is increased and speculative perceptions are decreased. The moderator of Shariah compliance mostly amplifies demand-side, certification, governance, and offering effects, albeit to a lesser extent.Novelty; This research is one of the early studies to systematically include Shariah compliance as a moderating variable in IPO research. It combines signaling and certification theories with ethical finance principles, thus connects traditional IPO literature with Islamic and sustainable finance.Research Implication; Practical Implication: Will also provide any investors who are looking for social responsible investments and also the regulators, who wanted to embed ethical terms in the governance of the capital market at world level.The originality of review: This study will contribute to academic theory by further an extention from an imformation symptomy perspective with ethical finance M and suggesting practical advice.